The Microbiome in Health and Disease from the Perspective of Modern Medicine and Ayurveda - Wallace, Robert Keith (Medicina (Kaunas), 2020)
The role of the microbiome in health and disease helps to provide a scientific understanding of key concepts in Ayurveda. We now recognize that virtually every aspect of our physiology and health is influenced by the collection of microorganisms that live in various parts of our body, especially the gut microbiome. There are many external factors which influence the composition of the gut microbiome but one of the most important is diet and digestion. Ayurveda and other systems of traditional health have for thousands of years focused on diet and digestion. Recent research has helped us understand the connection between the microbiome and the many different prevention and therapeutic treatment approaches of Ayurveda.